Atividades de promoção da saúde: representações sociais de idosos institucionalizados - Carvalho, Telma Pelaes de (2018)
The change in the profile of contemporary families, due to the inclusion of women in the labor market, the lack of time or energy to coexist with the elderly at home, the absence of a family caregiver to support the elderly, and the substantial fall in family size, contributed to the elderly living in long-term care institutions for the elderly (ILPI). The term ILPI refers to establishments that provide assistance or advise the elderly to perform their basic activities of daily living. As the aging process is not homogeneous, some elderly people in the face of adversity or inability to perform daily activities require support from a caregiver. However, without family support or restricted support, the elderly and their families can find shelter in long-term care facilities. With the objective of knowing the social representations of institutionalized elderly people about health promotion activities, mediated by language, the present study, which is descriptive in character, is anchored in the Theory of Social Representations (TRS). In this direction, the Organization of Health Promotion Groups (GPS) was conceived as an instrument capable of contributing to the development of autonomy and the improvement of the living and health conditions of institutionalized elderly people. For data collection, we used semi-structured interviews, whose results were processed by the IRAMUTEQ software, which applied statistical analysis to qualitative textual data. Of the 14 elderly participants in the research, 13 were women, aged between 60 and 92 years. The IRAMUTEQ software concentrated the speeches of the elderly in five classes, so named: 1 - Talk to know who are the people; 2 - It is still possible to take care of health; 3 - Participate in the meeting_ meeting helps to face the institutionalized life; 4 - Talking makes me feel better and, 5 - Knowing the other elderly people has improved our coexistence. In the analysis, 82.77% of the text segments were used, which shows that the classes were stable, that is, composed of units of text segments with similar vocabulary. The sum of all classes totaled 100%, and, within this percentage, classes 01 and 04 totaled 33.75% of the amount, highlighting and indicating resonance, complementarity and convergence of the statements of elderly participants about the importance of interactional activities, mediated by language for health promotion among participants. The statements made by the participants reveal that social interaction promotes the production and exchange of knowledge, the strengthening of interpersonal relationships, the sharing of lived experiences, and the establishment of mutual trust. The organization of the health promotion group, based on the theory of social representations, has proved to be effective for the development of language-mediated health promotion practices, enabling the elderly to (re) signify life by helping them to understand institutionalized old age